The Inquiry Skills of Teachers in Elementary School - Ucu Rahayu; Rif'at Shafwatul Anam; Mestika Sekarwinahyu; Amalia Sapriati (Jurnal Ilmiah Sekolah Dasar, 2022)
Inquiry skills are important skills possessed by a teacher. This study aims to analyze the inquiry skills of elementary school teachers and analyze the need for developing these skills in the lecture process in the elementary school teacher. This study uses a quantitative descriptive method with a survey design. Participants in this study amounted to 49 teachers. Data was collected using test instruments given to participants and interviews about their understanding of inquiry-based learning. Then the answers are analyzed and classified. The results showed that the teacher's inquiry skills needed to be improved because of the four groups of inquiry skills, both conceptualizing and planning design, implementation, analysis and interpretation, and communicating all were in the "weak" category, this was indicated by the average percentage of respondents in each group below 50%. The majority of respondents do not have a science education background. They also do not have sufficient knowledge about inquiry-based learning, especially in using it in the learning process. However, they agree that inquiry skills are important skills to be developed for students. Therefore, we need a lecture program that can facilitate elementary school teachers to be able to develop their inquiry skills so that science learning in elementary schools can be even more optimal.